2021
DOI: 10.1177/17585732211024182
|View full text |Cite
|
Sign up to set email alerts
|

Survivorship of anatomic press-fit short-stem radial head replacement with a pyrocarbon bearing

Abstract: Background Restoring the radial head as a stabiliser of the elbow is considered important in cases where there is an associated bony or ligamentous injury. A variety of radial head prostheses are available. There are no reports of the survivorship of a short-stem press-fit radial head prostheses with pyrocarbon bearing. Patients and methods With institutional review board approval, a retrospective case-note analysis was performed of a consecutive single-surgeon case series of the Integra LifeScience pyrocarbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Only 1 other article concerning this prosthesis has been recently published, by Viswanath and Watts. 28 They described similar results with 36 patients. A mean flexion arc of 105° and prono-supination of 148° was achieved; 10 stems had lucency, and 4 were revised.…”
Section: Discussionsupporting
confidence: 61%
“…Only 1 other article concerning this prosthesis has been recently published, by Viswanath and Watts. 28 They described similar results with 36 patients. A mean flexion arc of 105° and prono-supination of 148° was achieved; 10 stems had lucency, and 4 were revised.…”
Section: Discussionsupporting
confidence: 61%
“…5,[9][10][11][12][13] Previous studies have urged caution with use of monopolar press-fit designs over concerns with radiological loosening. [24][25][26] However, although radiographic changes have been previously observed with this prosthesis, their impact on longer term clinical outcomes have been less clearly defined. 9-13 Sallakh et al 12 at mean follow-up 42 months, reported all 12 patients with good-excellent clinical outcomes with no significant radiographic changes with regard to proximal migration, radiocapitellar arthritis or capitellar osteopenia, and no cases of prosthesis removal.…”
Section: Discussionmentioning
confidence: 99%